Prevención y complicaciones de infección de vías urinarias en pacientes pediátricos. Hospital Instituto Ecuatoriano de Seguridad Social. Riobamba. 2018- 2020 - Dennise Michelle, Muriel Pérez, Evelyn Paola, Vallejo Bravo (2021)
ABSTRACT Introduction: Urinary tract infection is one of the most prevalent pediatric ages, responsible for 7.8% of all febrile symptom’s visits. In Ecuador, it is the second cause of pediatric consultation after respiratory diseases. Several risk factors leading to urinary tract infection have been described. Objective: The primary purpose of the research is to determine whether prevention strategies are associated with the development of complications urinary tract infection in pediatric patients Hospital IESS Riobamba in the period 2018-2020. Methodology: The research was carried out using a descriptive, retrospective, cross-sectional study. The data were collected using the database of patients admitted to the pediatric area in the aforementioned period. Results: 104 cases of urinary tract infection were presented, showing that the population with the most significant involvement was adolescents and preschoolers. Only 1.9% were given hygiene measures as prevention at hospital discharge. Conclusions: There are multiple risk factors associated with urinary tract infection and the complications associated with them; prevention measures are a set of actions that must be applied to reduce the rate of reinfection due to this pathology. Keywords: Risk factors, Prevention, Reinfection. Reviewed by: Mgs. Sonia Granizo Lara. English professor. c.c. 0602088890